THU0159 Beneficial Effect of Methotrexate in Combination with a Biotherapy for the Long Maintenance of Biotherapy in RA Patients. (23rd January 2014) - Hilaire, C.; Pallot-Prades, B.; Collet, P.; Amouzougan, A.; Locrelle, H.; Thomas, T.; Marotte, H.
Abstract : Background: At this time, no predictive factor for response to biotherapy in RA patients is available in the daily practice. Objectives: The objective is to determine predictive factors for the first biological maintenance in rheumatoid arthritis (RA) treatment. Methods: From our database including 663 RA patients, 289 RA patients were received their first biotherapy between 2000 and 2009. Among these 289 RA patients, we selected 2 subsets of patients. In the first group, RA patients received the same biological therapy for at least 3 years (n=56). In the second group, RA patients required at least 3 different biological therapies over the 3 years following the first biological (n=36). Demographic parameters (age, sex, smoking, body mass index), RA activity (DAS28), biological parameters, DMARDs and glucocorticoid therapy were recorded. Chi-squared statistical analysis and odds ratios (OR) were performed. Results: Due to the follow-up of three years, TNFa blockers were mainly used as first biotherapy (Etanercept, adalimumab, or infliximab) in 93%. Biotherapies were equally distributed in both groups. Demographic parameters and disease ac tivity were similar in the two groups. In the same way, biological parameters of RA severity were not different in both groups. However, combination of DMARDs before starting the first biotherapy was associated with requirement to switch frequently biotherapy compared to the first goup (OR = 4.2; 95%CI: 1.193 to 14.79; p<0.05). However, in patients receiving DMARDs, using MTX compared to other DMARDs was associated with the maintenance of the first biological therapy (OR = 3.9; 95%CI: 1.216 to 11.55; p<0.01). Conclusions: Our study shows that the presence of méthotrexate at the starting time of a biotherapy is a factor for maintenance of the first biological therapy for at least three years. However, our result is mainly relevant for TNFa blockers which was the mainly biotherapy used at the first line. Disclosure of Interest: None Declared